2017
DOI: 10.1159/000481242
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Newly Proposed Time to Transarterial Chemoembolization Progression in Intermediate-Stage Hepatocellular Carcinoma Cases

Abstract: Background/Aim: Determination of failure of transarterial chemoembolization (TACE) for treatment of Barcelona Clinic Liver Cancer stage B (BCLC-B) hepatocellular carcinoma (HCC) has become important because of the development of tyrosine kinase inhibitor (TKI) treatment. We evaluated the usefulness and efficacy of the newly proposed time to TACE progression (TTTP). Patients and Methods: From 2006 to 2016, 192 BCLC-B HCC patients [median age 72 years, male/female ratio = 149/43, Child-Pugh score 5/6/7 = 106/56/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
(49 reference statements)
2
17
0
Order By: Relevance
“…Evaluation of TACE refractory status is important to select other therapeutic options such as a tyrosine kinase inhibitor . Moreover, TTTP is proposed as a prognostic predictor in patients undergoing repeated TACE . In the present study, CPMI was also associated with the TACE period as well as OS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Evaluation of TACE refractory status is important to select other therapeutic options such as a tyrosine kinase inhibitor . Moreover, TTTP is proposed as a prognostic predictor in patients undergoing repeated TACE . In the present study, CPMI was also associated with the TACE period as well as OS.…”
Section: Discussionmentioning
confidence: 89%
“…Transcatheter arterial chemoembolization (TACE) is standard therapy for patients with intermediate‐stage HCC . Transcatheter arterial chemoembolization is generally repeated until an insufficient response occurs during relatively long‐term treatment, and time to TACE progression (TTTP) is a prognostic predictor of patients treated with TACE . However, the effect of skeletal muscle mass on mortality or TTTP is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we believe that TTTP could be a good surrogate for OS as a primary endpoint in clinical trials of TACE. Izumoto et al [20] confirmed that TTTP is indeed a good surrogate for OS in trials of TACE.…”
Section: Lessons Learned From Negative Trials About Primary Endpointsmentioning
confidence: 99%
“…A number of reports, such as the global observational study OPTIMIS and 2 other studies, indicate that repeated TACE procedures lead to a deterioration of liver function in up-to 7 criteria out patients [56,57,[73][74][75]. In terms of liver function, ALBI grade 2 especially mALBI grade 2b is a poor prognostic factor for OS after TACE [73,75].…”
Section: Tace-unsuitablementioning
confidence: 99%